2017
DOI: 10.1177/1057083717723919
|View full text |Cite
|
Sign up to set email alerts
|

Developing the Emotional Intelligence of Undergraduate Music Education Majors: An Exploratory Study Using Bradberry and Greaves’ (2009) Emotional Intelligence 2.0

Abstract: Research focused on the relationship of emotional intelligence (EI) to academic and professional success in education, and whether and how it might be taught and learned, is inconclusive. The purpose of this study was to examine the degree to which undergraduate music education majors experienced a change in EI after implementing strategies from Emotional Intelligence 2.0. Participants included 10 junior-year music education majors enrolled in a semester-long music teaching foundations course. Participants pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 14 publications
2
13
0
1
Order By: Relevance
“…However, as these traits are relatively stable, it is possible that people will come back to their "baseline" after a while if the competencies are not practised." In support of Boyatzis and Sattcioglu's (2008) original findings, more recent research has confirmed the positive impact that EI coaching can have on individual social and emotional competencies; however, due to the recency of this research the longevity of these effects is still unknow (Gilar-Corbí et al, 2018;McGinnis, 2018;Wang, 2019).…”
Section: Emotional Intelligence In Third Level Settingssupporting
confidence: 59%
See 2 more Smart Citations
“…However, as these traits are relatively stable, it is possible that people will come back to their "baseline" after a while if the competencies are not practised." In support of Boyatzis and Sattcioglu's (2008) original findings, more recent research has confirmed the positive impact that EI coaching can have on individual social and emotional competencies; however, due to the recency of this research the longevity of these effects is still unknow (Gilar-Corbí et al, 2018;McGinnis, 2018;Wang, 2019).…”
Section: Emotional Intelligence In Third Level Settingssupporting
confidence: 59%
“…Therefore, third level colleges are increasingly focusing on providing students with rounded instruction that includes the development of social and emotional skills. Many college courses now include dedicated modules in areas such as personal development that to varying degrees incorporate emotional intelligence coaching (McGinnis, 2018;Wang, 2019). EI coaching is also increasingly being offered to students as an extracurricular support and there is a growing body of evidence attesting to the value of doing so.…”
Section: Emotional Intelligence In Third Level Settingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Psychological health includes the capacity to maintain a sense of autonomy, self-acceptance, and personal development, as well as a sense of life purpose and self-esteem ( Smith, 2021 ). Maintaining a healthy mind involves more than just treating or preventing mental illness ( McGinnis, 2018 ). The majority of people listen to music at certain point in their lives.…”
Section: Research Literaturementioning
confidence: 99%
“…Inteligência Emocional (IE) envolve gerenciar as próprias emoções (SMITH et al, 2018), mas também é comumente definida como a capacidade de perceber emoções em si e nos outros, entender emoções, integrar emoções para facilitar o pensamento e regular emoções para o crescimento pessoal (SALOVEY; MAYER, 1990;MCGINNIS, 2018).…”
Section: Introductionunclassified